Detection of specific periodontal microorganisms from bacteraemia samples after periodontal therapy using molecular-based diagnostics (2011)
The aim of this study was to assess the presence of subgingival pathogens in peripheral blood samples from periodontitis patients before and after scaling and root planing (Sc/RP) using nested polymerase chain reaction (nested PCR). Peripheral blood samples were obtained from 42 patients with severe generalized chronic or aggressive periodontitis. In each patient, four samples of peripheral blood were drawn at different times: immediately before the Sc/RP procedure; immediately after Sc/RP; 15 and 30 min. post‐Sc/RP. Blood samples were analysed for bacteraemia with anaerobic culturing and nested PCR, using universal bacterial primers that target the 16S‐rRNA gene of most bacteria, subsequently re‐amplified with specific primers to Porphyromonas gingivalis , Aggregatibacter actinomycetemcomitans , Tannerella forsythia , Eikenella corrodens , Campylobacter rectus and Prevotella intermedia , using a modified phenol–chloroform method for DNA extraction. Presence of specific periodontal pathogens in peripheral blood after treatment was detected in 54.8% of the patients, in 47.6% with anaerobic culturing and in 19% with nested PCR. In 16.6%, the periodontal pathogens were detected before Sc/RP. P. gingivalis and A. actynomicetemcomitans were the pathogens most frequently detected in the bloodstream before and after Sc/RP. Nested PCR demonstrated the presence of DNA from periodontal pathogens in blood samples in severe periodontitis patients before, during and after periodontal therapy. The use of these molecular‐based techniques may improve the accuracy from the results obtained by haemoculture.